University of Ghana Distance Education Programme and Female Students: Implications for family Well-Being - Biney, I.K. (International Journal of Innovative Research and Development, 2016)
Globally, governments are educating their people by increasing student intake into universities through distance education. This approach of increasing access to universities has the potential of increasing the number of students in universities, including females. In the 2007/2008 academic year, out of a total of 906 students enrolled in the University of Ghana Distance Education (UG-DE) programme to pursue undergraduate degree courses, only 270 were females. In the 2011/2012 academic year, however, out of a total of 8,163 students enrolled, 2,938 were females, and 5,225 were males putting the female students’ enrolled figure more than half the number of male students admitted. This exploratory study examined the implications of increasing female student enrolment on the UG-DE programmes for their families’ well-being. Views were solicited from 30 female students through semi-structured interviews. Female students held the view that their education would impact positively on their children’s education, health status and future prospects. It recommends that the University of Ghana should expedite work on the re-introduction of the access courses to encourage more female enrollment into undergraduate degree programmes through UG-DE to engender family well-being.
Keywords: Higher education; distance learning; female students; families’ well-being